Ablation index‐guided 50 W ablation for pulmonary vein isolation in patients with atrial fibrillation: Procedural data, lesion analysis, and initial results from the FAFA AI High Power Study. (13th October 2019) - Chen, Shaojie; Schmidt, Boris; Bordignon, Stefano; Urbanek, Lukas; Tohoku, Shota; Bologna, Fabrizio; Angelkov, Lazar; Garvanski, Iskren; Tsianakas, Nikolaos; Konstantinou, Athanasios; Trolese, Luca; Weise, Felix; et al.
Abstract: Background: Radiofrequency high‐power ablation appears to be a novel concept for atrial fibrillation (AF). The ablation index (AI) value has been associated with durability of pulmonary vein isolation (PVI). Objectives: This study aimed to report the procedural data and initial results of a combined ablation technique using AI‐guided high‐power (AI‐HP; 50 W) ablation for PVI. Methods: Symptomatic AF patients were consecutively enrolled and underwent wide‐area contiguous circumferential PVI. Contact‐force catheters were used, ablation power was set to 50 W targeting AI values (550 anterior and 400 posterior). Esophageal temperature was monitored during procedure, all patients underwent postablation esophageal endoscopy. Results: PVI was achieved in all (n = 50, mean age: 68 ± 9 years, female: 60%) patients, rate of first‐round PVI was 92%. A total of N = 2105 AI‐guided ablation lesions were analyzed. Comparing left anterior wall vs left posterior wall and right anterior wall vs right posterior wall, mean ablation time (s) per lesion was 20.5 ± 8 vs 8.6 ± 3 and 12.2 ± 4 vs 9.3 ± 3; mean contact force (g): 17.1 ± 12 vs 25.4 ± 14 and 33.7 ± 13 vs 21.0 ± 11; mean AI: 547 ± 48 vs 445 ± 55 and 555 ± 56 vs 440 ± 47 (all P  < .0001). Procedure and fluoroscopy time (minute) were 55.6 ± 6.6 and 6 ± 1.7, respectively. Only one (2%) patient had a minimal esophageal lesion. During In‐hospital and 1‐month follow‐up no major complications such as death, stroke, tamponade, or atriaesophageal fistula (AE) occurred. Preliminary 6‐month follow‐up showed 48 of 50 (96%) patients were free from clinical AF/atrial tachycardia recurrence. Conclusion: AI‐HP (50 W) ablation appears to be a feasible, safe, fast, and effective ablation technique for PVI.